Monoclonal antibody against PACAP. The future of migraine prevention? - Imran, Raafey (Journal of the Pakistan Medical Association, 2025)
Dear editor, Migraine is a common and often disabling neurovascular condition that affects around 15% of the world’s population, and the actual number might be even higher [1]. Its triggers range widely, from stress and hormonal shifts to fasting and changes in the weather [2]. With so many affected and such varied causes, it’s no surprise that migraines take a toll, not just on individuals but also on economies. For example, in the United Kingdom alone, lost productivity linked to migraines has been estimated at over £5.8 billion each year [3]. There are many options available for migraine prevention, like beta-blockers, anticonvulsants, and antidepressants. But these treatments often come with a trade-off. Patients may experience side effects like fatigue, weight gain, or low blood pressure, which can make it hard to stick with the regimen [4]. On top of that, people with other health issues—such as asthma, COPD, or liver disease—might not be able to take these drugs safely. Those already on SSRIs also face limited choices, since they can’t use certain medications like triptans or MAOIs due to the risk of dangerous interactions. Recently, researchers started exploring a different treatment approach: monoclonal antibodies that block pituitary adenylate cyclase-activating polypeptide (PACAP). One such treatment, Lu AG09222, was tested in a recent randomized trial of 237 patients. According to Ashina et al., patients who received this therapy had fewer migraine days, attacks, and headache episodes compared to those who didn’t. The main side effect reported was fatigue, and importantly, no serious safety concerns came up [5]. Even with these promising results—especially for patients who don’t tolerate standard drugs—the cost of monoclonal antibody treatments remains a major hurdle. Unless access improves or prices come down, many who could benefit may not be able to afford them.